Surface alloying of Al films/Ti substrate based on high-current pulsed electron beams irradiation; Rare Metals; Vol. 33, iss. 2 - Mei X. X.; Fu J. Q.; Li X. N.; Rotshtein V. P.; Koval N. N. Nikolay Nikolaevich; Ma T. C. (2014, 2014)
Title screen